2022
DOI: 10.1186/s43088-022-00310-3
|View full text |Cite
|
Sign up to set email alerts
|

In silico detection of Cucurbitacin-E on antioxidant enzymes of model organism Galleria mellonella L. (Lepidoptera: Pyralidae) and variation of antioxidant enzyme activities and lipid peroxidation in treated larvae

Abstract: Background In silico studies further provided predictive binding properties of selected ligands for inhibition of target protein. In the study, molecular binding poses of Cucurbitacin-E and antioxidant enzymes (glutathione-S-transferase (GST), superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx) and acetylcholinesterase (AChE) of Galleria mellonella were determined in silico. Cucurbitacins are the most important components of Ecballium elaterium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Zorlu et al (2018) found that titanium dioxide nanoparticles included in the G. mellonella diet had a dose-dependent toxic effect and increased resistance to oxidative stress at low concentrations. Increasing doses of Cucurbitacin-E essential oil caused decreasing in SOD, CAT, GST GPx, GR, and AChE activities and increasing in MDA levels (Ercan et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Zorlu et al (2018) found that titanium dioxide nanoparticles included in the G. mellonella diet had a dose-dependent toxic effect and increased resistance to oxidative stress at low concentrations. Increasing doses of Cucurbitacin-E essential oil caused decreasing in SOD, CAT, GST GPx, GR, and AChE activities and increasing in MDA levels (Ercan et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…There are limited studies on the effects of medicinal plant extracts on G. mellonella immunity. Some plant extracts cause a decrease in the antioxidant enzyme activity of G. mellonella (Ercan et al, 2022), and this decrease is probably due to the effect of plant secondary metabolites. It was determined that Helichrysum arenarium increased cell-mediated immunity at low doses in G. mellonella larvae at certain doses and had no effect outside this range (Kaya et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The polyphagous cotton leafworm, Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae), is widespread. It can feed on over 100 host plants and can cause yield losses of up to 50% due to the larvae's leaf-consuming activity (Russell et al 1993, EPPO 2018. As a result of its resistance and cross-resistance to chemical pesticide, S. littoralis has become difficult to control (Quesada-Moraga et al 2006, Siegwart et al 2015.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Chemical stress can lead to oxidative damage and oxidative stress ( Kodrík et al 2015 ). Therefore, insects possess enzymatic and nonenzymatic defense systems against chemical stress, which might stop the harmful effect of the reactive oxygen species (ROS) on cells ( Ercan et al 2022 ). The main antioxidant enzymes in insects that have been linked to insect defense systems are superoxide dismutase (SOD) and catalase (CAT) ( Li et al 2017 , Awad et al 2022 , Moustafa et al 2022 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation